Professional issues in secondary teaching - Carrie Mercier; Helen Scott; Carey Philpott (India : Sage Publication, 2013)
Becoming a secondary teacher requires an understanding of a range of teaching issues, including concerns such as curriculum development and learning through observation in the classroom, alongside key conceptual aspects such as reflection and the nature of learning. This book looks at these issues alongside a range of other topics.
Chapter1. Introduction: Who is this book for, what is it for and how do I use it? / Carrie Mercier, Carey Philpott and Helen Scott -- Chapter2. Who has all the answers in education (and why should you believe them)? / Carey Philpott -- Chapter3. Is there more to lesson observation than meets the eye? What can you learn from watching others teach? / Helen Scott -- Chapter4. Why is critical reflection important? / Jon Tibke and Lindsey Poyner -- Chapter5. What is my professional identity? / Martyn Lawson and Martin Watts -- Chapter6. What is the role of the subject specialist in secondary education? / Kathryn Fox and Patrick Smith -- Chapter7. What do I need to know about the curriculum? / Carrie Mercier -- Chapter8. What is learning theory? How can it help me? / Tony Ewens -- Chapter9. How should I engage with classroom assessment? / Camilla Cole -- Chapter10. What is diversity and how can I respond to it? / Joy Schmack -- Chapter11. How do we promote the spiritual, moral, social and cultural development of pupils and how does this relate to community cohesion? / Carrie Mercier and Carolyn Reade -- Chapter12. How can I prepare for my NQT year? / Gail Fuller -- Chapter13. What can master's-level study do for me? / Helen Scott -- Chapter14. Conclusion: How does it all fit together and what do I need to do now? / Carey Philpott.
includes index.
Keywords: EDUCATION